Pengaruh Penambahan Semen Terhadap Kuat Geser Lempung Sebelum Dan Sesudah Penjenuhan - Ali, Miftahul; Satibi, Syawal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Soil is a material that very influential in the contruction work. Major issues in soft soil are low bearing capacity and high settlement condition. One of soil stabilitation effort is mixing PCC cement in specific content by the soil to improve shear strength. This research aims to study UCS and CBR values of mixed clay and cement at 2%, 3%, 4% and 5% content variations on soaked condition. The result showed that increasing cement content until 5% mixture raising soil dry density still optimum mouisture content decrease. While over 5% cement mixture showed contrary behavior. UCS and CBR values not influenced by soaking process.Key Words: CBR,UCS, clay, cement